Effects of Buprenorphine on Liver Enzymes in Patients without a History of Liver Disease - Maryam Rezaei; Shahnaz Yousefizadeh (Fasa University of Medical Sciences, 2022)
Background & Objective: Buprenorphine (BUP), a synthetic opioid, treats pain and opioid use syndrome. The potential of BUP to cause liver toxicity has not been fully evaluated. The present literature review was designed to investigate the impact of BUP treatment on liver function in patients without a previous history of liver diseases. Materials & Methods: A literature review was implemented within databases of Scopus, PubMed, ISI, and Cochran until February 2022. Studies published in English were included in this study. Retrieved citations were screened and data were extracted by at least two independent reviewers. Results: Of the 1853 studies screened citations, 14 research reports were eligible. Overall, among the randomized controlled trial, four studies reported hepatotoxicity in patients who had a history of hepatitis C or hepatitis B seroconversion under BUP treatment. Conclusion: No strong evidence was found for hepatotoxicity of BUP in this study. Elevation in the liver enzyme levels in some patients may be related to other factors such as infectious diseases, illicit drugs, alcohol consumption, environmental pollutants, and chronic diseases. More experimental and clinical studies should be conducted to address this question.